1999
DOI: 10.1093/humupd/5.5.393
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and effects of male genital tract infection on sperm quality and fertilizing potential: the andrologist's viewpoint

Abstract: There are several mechanisms acting in synergism that can impair sperm characteristics of patients with accessory gland infection. In some cases, conventional sperm variables are disturbed with oligo and/or asthenozoospermia. In other patients, these sperm variables may appear normal, but the functional capacity of spermatozoa may be impaired. In particular, changes in the composition of the sperm membrane may result in reduced acrosome reactivity and capacity to fuse with the oolemma, and oxidative damage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
1
9

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(128 citation statements)
references
References 66 publications
1
114
1
9
Order By: Relevance
“…Male genital tract infections can have an influence on semen parameters via different mechanisms (Comhaire et al, 1999), including a direct disruption of spermatogenesis by chronic orchitis (Schuppe et al, 2008) or histomorphological changes potentially leading to obstructive oligo-/azoospermia (Heshmat and Lo, 2006).…”
Section: Paternal Age and Infectionsmentioning
confidence: 99%
“…Male genital tract infections can have an influence on semen parameters via different mechanisms (Comhaire et al, 1999), including a direct disruption of spermatogenesis by chronic orchitis (Schuppe et al, 2008) or histomorphological changes potentially leading to obstructive oligo-/azoospermia (Heshmat and Lo, 2006).…”
Section: Paternal Age and Infectionsmentioning
confidence: 99%
“…A large clinical study indicated that more than 80 % of infertile men have sperm-motility defects [7]. The causes of poor sperm motility include structural defects in the sperm tail, functional defects of the epididymis or other accessory sex glands, and abnormal metabolism in the testicular tissue and/or epididymis [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which leukocytes may determine decreased fertility potential is due to the release of reactive oxygen species (ROS), oxygen molecules with an unpaired electron [2,[4][5][6]. While baseline ROS concentration is essential during sperm capacitation and acrosome reaction [7,8], excessive ROS production will lead to oxidative stress [9,10], which in turn will decrease sperm functional integrity (mitochondrial activity, sperm-egg binding, and DNA integrity, for example) [11,12].…”
Section: Introductionmentioning
confidence: 99%